Gilbert y las líneas de fuerza de Faraday: una recontextualización histórica para la enseñanza del magnetismo - Bravo Villamil, Magali (Revista Científica, 2011)
It is intended recognize the importance of organization and construction of sensorial experiences that allow questions, to make way for the construction of explanations of meaningful for the subject (students and teachers). To demonstrate this in the history of physics, it is reviewed the work of Gilbert's and Faraday's papers to identify some aspects of magnetism that can be brought into the classroom and generate discussion about common presentations are displayed in the school textbooks. With this inquiry we expect that the history of physics provides several tools that allow the teacher to make sense of physics in the classroom,as well the work of teachers.The other side and not least, I will be shown the process of construction of explanations, is in continuous connection with sensory experience,